SOME ASPECTS OF COLLATERAL LENDING IN THE REPUBLIC OF UZBEKISTAN - Dildora Shukhratovna Mirdjalilova; Inomjon Ortikbayevich Karimov (Galaxy International Interdisciplinary Research Journal, 2021)
The article discusses the practice of assessing collateral for bank loans. The main recommendations on the results of the analysis of the state of the issue are given.